The Role of Quranic Therapy in Treating Anxiety and Depression - Wijaya, Wijaya; Labib, Hakki Akmal; Dahlan, Bayani; Ilham, Ilham; Putra, Sudarmadi (Journal International Dakwah and Communication, 2024)
The rising prevalence of anxiety and depression has led to an increasing interest in alternative therapeutic methods, especially those rooted in spiritual and religious practices. Quranic therapy, based on recitation and reflection upon the verses of the Quran, has been increasingly recognized for its potential in treating mental health conditions. This research aims to explore the effectiveness of Quranic therapy in alleviating anxiety and depression. The study utilizes a mixed-methods approach, combining qualitative and quantitative methods. Participants were exposed to a structured regimen of Quranic recitation and reflection for a period of six weeks. Psychological assessments were conducted before and after the intervention, including scales for measuring anxiety and depression. The findings indicate a significant reduction in symptoms of both anxiety and depression, with participants reporting improvements in their overall emotional well-being. Moreover, qualitative feedback highlighted the spiritual connection and calming effects experienced by participants during Quranic therapy sessions. The study concludes that Quranic therapy can serve as a complementary approach in mental health treatment, promoting spiritual healing alongside traditional psychological therapies. Further research is needed to understand the mechanisms behind this therapeutic effect and its long-term benefits.